Populism, punishment and the threat to democratic order: the return of the strong men - Pratt, John (Routledge studies in crime and society, 2023)
"This book traces the rise of contemporary populism in Western democracies, marked by the return of would-be 'strong men' politicians. It seeks to make sense of the resultant nature, origins, and consequences -as expressed, for example, in the startling rise of the social movement surrounding Trump in the US, Brexit in the UK and the remarkable spread of ideologies that express resistance to "facts," science, and expertise. Uniquely, the book shows how what began as a form of penal populism in the early 1990s transformed into a more wide ranging populist politics with the potential to undermine or even overthrow the democratic order altogether; examines the way in which the Covid-19 pandemic has impacted on these forces, arguing it threw the flailing democratic order an important lifeline, as Vladimir Putin has subsequently done with his war in Ukraine. The book argues that contemporary political populism can be seen as a wider manifestation of the earlier tropes and appeal of penal populism arising under neo-liberalism. The author traces this cross over and the roots of discontent, anxiety, anti-elites sentiment and the sense of being forgotten, that lie at the heart of populism, along with its effects in terms of climate denial, 'fake news', othering, nativism and the denigration of scientific and other forms of expertise. In a highly topical and important extension to the field the author suggests that the current covid pandemic might prove to be an 'antidote' to populism, providing the conditions in which scientific and medical expertise, truth telling, government intervention in the economy and in health policy, and social solidarity, are revalorised. Encompassing numerous subject areas and crossing many conventional disciplinary boundaries, this book will be of great interest to students and scholars of criminology and criminal justice, sociology, political science, law, and public policy"--